Technical efficiency of cacao (Theobroma cacao L) cultivation in the south of Córdoba, Colombia - Martínez Reina, Antonio María (2024)
The southern region of the department of Córdoba, Colombia, in the last ten years has shown growth in the cultivation of cocoa (Theobroma cacao L.) as an alternative to replace illicit crops and improve the quality of life of the families that They have gone through armed conflict. The production system has shown potential given its yields that exceed the national average; However, there is no evidence of the presence of a study that investigates the efficiency in the allocation or investment of resources. The objective of the work was to determine the technical efficiency of this crop with information obtained from a structured survey applied to 158 cocoa farmers in the municipalities of Puerto Libertador, Montelíbano, Tierralta and Valencia. The information obtained contained technical and socioeconomic variables that allowed calculating the current state of the technical efficiency of cocoa cultivation for this region of the country. The technique used was the stochastic frontier through the estimation of parameters by the least squares method to a Cobb Douglas type production function. Although the yields are not low, the results show that the farmer has a technical efficiency of 39%, attributed to underutilization of resources resulting in a production gap. It is concluded that this inefficiency is also associated with social factors such as the advanced age of farmers and low levels of schooling, mainly.